2009
DOI: 10.1152/ajpheart.00124.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-negative p38α mitogen-activated protein kinase prevents cardiac apoptosis and remodeling after streptozotocin-induced diabetes mellitus

Abstract: The p38 mitogen-activated protein kinase (MAPK) is activated during heart diseases that might be associated with myocardial damage and cardiac remodeling process. Diabetic cardiomyopathy is associated with increased oxidative stress and inflammation. The purpose of this study was to investigate the role of p38alpha MAPK after experimental diabetes by using transgenic (TG) mice with cardiac-specific expression of a dominant-negative mutant form of p38alpha MAPK. The elevation of blood glucose was comparable bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 54 publications
(72 reference statements)
12
64
0
Order By: Relevance
“…Throughout the process of apoptosis, proteins of the caspase and Bcl-2 families have crucial roles. Apoptosis is an important mechanism of myocardial cell damage in diabetic disease, and proteins of the caspase and Bcl-2 families are also involved (Li et al, 2008;Chen et al, 2009;Liu et al, 2009;Thandavarayan et al, 2009). CASP3 is a member of the caspase family and has been recognized as an important initiator and promoter of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the process of apoptosis, proteins of the caspase and Bcl-2 families have crucial roles. Apoptosis is an important mechanism of myocardial cell damage in diabetic disease, and proteins of the caspase and Bcl-2 families are also involved (Li et al, 2008;Chen et al, 2009;Liu et al, 2009;Thandavarayan et al, 2009). CASP3 is a member of the caspase family and has been recognized as an important initiator and promoter of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen was found to exert a protective effect in cardiomyocytes related to induction of the Bcl-xL gene (Morrissy et al, 2010). Many signaling pathways, such as p38 and MitogenActivated Protein Kinase (MAPK), may prevent apoptosis of cardiomyocytes in an STZ-induced model of DM via up-regulation of Bcl-xL protein expression (Thandavarayan et al, 2009). Our study showed that treatment with ginsenoside Rg1 could restore myocardial protein levels of Bcl-xL in a dose-dependent manner, suggesting that regulation of Bcl-2 family proteins may be involved in the antiapoptotic effect of Rg1 in diabetic myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of p38-MAPK pathway also impairs insulin action into the myocardium increasing free radical-mediated infarction [78]. Diabetic mice with abbrogated gene expression of the p38-MAPK had decreased levels of free radical production as well as lower degree of myocardial damage and apoptosis compared with normal gene expression mice [79]. Cardiomyocytes were protected against oxidative stress-induced hyperglycemic toxicity through inhibition of the p38-MAPK signaling pathway [80].…”
Section: Molecular Pathways Of Diabetes Mellitus Pathogenesismentioning
confidence: 99%
“…The formation of hydroxyl radical (ÁOH) was detected with 5,5 0 -dimethyl-1-pyrroline-1-oxide (DMPO) as a spin trap [3,21]. The hearts were homogenized in cold PBS (100 mg hearts/ml), incubated with 200 μmol/L Dox (group V and Sch B treated) or without Dox (group N) for 10 minutes, and then added to 0.05 ml of 9.0 mol/L DMPO.…”
Section: Electron Spin Resonance (Esr) Spectroscopymentioning
confidence: 99%